2016
DOI: 10.1146/annurev-soc-081715-074246
|View full text |Cite
|
Sign up to set email alerts
|

Race and Politics in the Age of Obama

Abstract: Due to a preoccupation with periods of large-scale social change, nationalism research had long neglected everyday nationhood in contemporary democracies. Recent scholarship, however, has begun to shift the focus of this scholarly field toward the study of nationalism not only as a political project but also as a cognitive, affective, and discursive category deployed in daily practice. Integrating insights from work on banal and everyday nationalism, collective rituals, national identity, and commemorative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 113 publications
0
38
1
Order By: Relevance
“…Contrary to a stream of scholarly literature pointing to a process of 'racialization of politics' (e.g. Tesler, 2012Tesler, , 2013Parker, 2016, with particular reference to the case of president Obama), we argue that, when prejudice is political, it should not be primarily interpreted as a form ofmore or less overt, more or less implicitracism. It is rather a form of partisan/ideological categorization, such as those occurring for any other issue which favors the emergence of 'sorted-by-party' attitudesfor example, from the Obama administration's health-care reform in the US, 2 to the 2016 constitutional referendum in Italy.…”
Section: Introductioncontrasting
confidence: 89%
“…Contrary to a stream of scholarly literature pointing to a process of 'racialization of politics' (e.g. Tesler, 2012Tesler, , 2013Parker, 2016, with particular reference to the case of president Obama), we argue that, when prejudice is political, it should not be primarily interpreted as a form ofmore or less overt, more or less implicitracism. It is rather a form of partisan/ideological categorization, such as those occurring for any other issue which favors the emergence of 'sorted-by-party' attitudesfor example, from the Obama administration's health-care reform in the US, 2 to the 2016 constitutional referendum in Italy.…”
Section: Introductioncontrasting
confidence: 89%
“…Under such circumstances, nationalist beliefs may manifest themselves in micro-interactions, as either sources of in-group cohesion or inter-group animosity, but not as primary features of electoral campaigns or voting behavior (though their downstream policy correlates may well be more salient). Occasionally, however, a confluence of structural conditions, particularly those that threaten existing ethnoracial status hierarchies, may bring disputes about the nation's meaning to the forefront of political claims-making and individual-level political preferences (Anderson 2016;Bobo 1999;Jardina 2019;McVeigh and Estep 2019;Parker and Barreto 2014;Parker 2016). Given the prominence of anti-minority discourse in contemporary radical-right politics, the current era appears to represent precisely such a conjuncture.…”
Section: Nationalist Cleavages In the United Statesmentioning
confidence: 99%
“…This perspective rests on the claim that economic anxiety is neither a necessary nor sufficient cause of voters' favorability toward candidates who capitalize on out-group antipathies. Instead, it is voters' deep-seated racism and xenophobia (Ivarsflaten 2008;Lucassen and Lubbers 2012;Mutz 2018;Sides et al 2018)-or a general distaste for multicultural and cosmopolitan cultural norms (Norris and Inglehart 2018)-that gives resonance to such campaign messages, especially under conditions of collective status threat (Bobo 1999;Parker 2016). In addition to furnishing correlations between the relevant attitudes and radical-right support, those favoring cultural explanations often point to the weaknesses of the economic framework: that radical-right supporters tend not to be the worst off in society, that they often oppose economic redistribution (especially if it involves benefits for the groups they dislike), and that racial segregation is a more typical characteristic of the areas in which these voters live than is having borne the brunt of economic decline (Sides et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The election of President Obama played a key role: research indicates that Obama's election led to increases in the rate of belief among white Americans, especially conservatives, that racism no longer exists. 2 At the same time, in the wake of his election, one third of white Americans indicated that they were "troubled" that a black man was President, the Tea Party movement emerged with antiminority rhetoric, resentment toward Democrats increased, support among whites for the Democratic party declined, and white support for addressing racial inequities decreased. 2 Obama's election also led to a marked increase in racial animosity expressed in social media: there was a proliferation of hate websites and anti-Obama Facebook pages, with the widespread use of historical racial stereotypes that are no longer seen in mainstream media.…”
Section: Incre a Sed R Acial Hos Tilit Ymentioning
confidence: 99%
“…2 At the same time, in the wake of his election, one third of white Americans indicated that they were "troubled" that a black man was President, the Tea Party movement emerged with antiminority rhetoric, resentment toward Democrats increased, support among whites for the Democratic party declined, and white support for addressing racial inequities decreased. 2 Obama's election also led to a marked increase in racial animosity expressed in social media: there was a proliferation of hate websites and anti-Obama Facebook pages, with the widespread use of historical racial stereotypes that are no longer seen in mainstream media. 3 The presidential candidacy of Donald Trump appeared to bring further to the surface preexisting hostile attitudes toward racial and ethnic minorities, immigrants, and Muslims.…”
Section: Incre a Sed R Acial Hos Tilit Ymentioning
confidence: 99%